Flexural Strength of Heat Cure Denture Base Resin incorporated with Curcumin: An In-Vitro Study - Khanal, LR; Shrestha, A; Joshi, KR; Bhochhibhoya, A (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: Acrylic resin when used for fabrication of denture is susceptible for microbial colonization. Many antimicrobial agents have proven effective against the microbial colonization when they were incorporated into the acrylic resin but adding anything into the acrylic resin can alter its mechanical properties resulting into unacceptable intraoral use. This study was done to evaluate ifadding an antimicrobial agent, Curcumin, alters the flexural strength of acrylic agent.Methods: 172 acrylic strips were fabricated. They were divided equally into 4 groups depending upon concentration of curcumin as Control, T1: 1% curcumin, T2: 3% curcumin and T4: 5% curcumin. Flexural strength was tested using 3-point bend test using Universal Testing Machine.Results: There was no significant difference in values of mean flexural strength for control, 1% and 3% curcumin groups. There was significant difference in the mean value between control and 5% curcumin group.Conclusion: 1% and 3% curcumin can be incorporated into acrylic resin without significantly altering its mechanical properties.